Influence of Seed Size and Sowing Depth on Emergence and Growth Performance of Salvadora oleoides in the Indian Thar Desert - Mertia, R. S.; Sinha, N. K.; Santra, Priyabrata; Singh, Daleep (Indian Forester, 2012)
Series of trials on Salvadora oleoides were conducted to standardize the package of practices for large-scale raising of seedlings for afforestation programmes in the Indian Thar desert with the major focus on the influence of seed size and sowing depth on seedling emergence and subsequent growth. Among different combinations of seed size and sowing depth, large sized seeds (â‰¥0.04 g) planted at 0.5 cm depth showed significantly higher emergence per centage, seedling height, leaves plant, and dry weight of seedling than other seed size and sowing depth combinations. The study revealed that placement of large sized seeds at shallow depth may result in successful raising of this species in nursery and thus may help in successful implementation of afforestation programmes in the Indian Thar desert.